2020
DOI: 10.7150/ijbs.32460
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of microRNA-9 enhances cisplatin sensitivity in hepatocellular carcinoma by regulating EIF5A2-mediated epithelial-mesenchymal transition

Abstract: We investigated the role of microRNA (miR)-9 in modulating chemoresistance in hepatocellular carcinoma (HCC) cells. MiR-9 was overexpressed or knocked down in HCC cell lines. Cell viability, cell proliferation, the expression of EIF5A2 and the epithelial-mesenchymal transition (EMT)-related proteins were examined. HCC cells overexpressing miR-9 were more sensitive to cisplatin; miR-9 knockdown yielded the opposite result. The in vivo nude mouse HCC xenograft tumors yielded the same results. EIF5A2 was identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…The study found that miR-9 enhanced the sensitivity of HCC cells to cetuximab via targeting eIF5A2. miR-9 can also enhance the sensitivity of HCC cells to cisplatin by targeting eIF5A2, resulting in inhibition of EMT signaling ( 59 ). Moreover, miR-383 underexpression-mediated doxorubicin resistance in HCC cells could be reversed by silencing eIF5A2 ( 60 ).…”
Section: Role Of Eif5a In Malignant Tumorsmentioning
confidence: 99%
“…The study found that miR-9 enhanced the sensitivity of HCC cells to cetuximab via targeting eIF5A2. miR-9 can also enhance the sensitivity of HCC cells to cisplatin by targeting eIF5A2, resulting in inhibition of EMT signaling ( 59 ). Moreover, miR-383 underexpression-mediated doxorubicin resistance in HCC cells could be reversed by silencing eIF5A2 ( 60 ).…”
Section: Role Of Eif5a In Malignant Tumorsmentioning
confidence: 99%
“…Accumulating studies have demonstrated that miRNAs serve vital roles in drug resistance for cancer chemotherapy based on their functions and targets ( 24 , 25 ). A previous study revealed that upregulation of miR-9-5p increased the sensitivity of hepatocellular carcinoma cells to cisplatin via modulating epithelial-mesenchymal transition by eukaryotic translation initiation factor 5A2 signaling ( 9 ). However, whether miR-9-5p is involved in 5-FU resistance of CRC is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al ( 8 ) demonstrated that miR-26b was involved in 5-FU-induced apoptosis in CRC. Recent studies have suggested that miR-9 behaves as a tumor suppressor in different types of cancer, such as hepatocellular carcinoma ( 9 ), gastric cancer ( 10 ), acute myeloid leukemia ( 11 ) and CRC ( 12 ). Cekaite et al ( 13 ) observed low miR-9-5p expression in CRC cells and found that miR-9-5p overexpression inhibits cell survival and promotes apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that miRNA regulatory networks played an essential effect on the progression and chemoresistance of cancer [ 32 , 33 ]. Liu et al showed that miR-497-5p enhanced apoptosis in OC cells [ 34 ].…”
Section: Discussionmentioning
confidence: 99%